Oral Health Interventions Using Chlorhexidine-Effects on the Prevalence of Oral Opportunistic Pathogens in Stroke Survivors: A Randomized Clinical Trial - Prof. Madya Dr. Normaliza Binti Ab Malik; Abdul Razak F.; Mohamad Yatim S.; Lam O.L.T.; Jin L.; Li L.S.W.; McGrath C. (Mosby Inc., 2024)
Objective: To evaluate the presence of oral opportunistic pathogens among stroke survivors, both before and after oral health care interventions. Methods: A multicenter randomized clinical trial was conducted on hospitalized stroke survivors. Those in the control group were given standard care of oral hygiene (a manual toothbrush and toothpaste), whereas those in the test group were given intense care of oral hygiene (a powered toothbrush and 1% chlorhexidine oral gel). Oral clinical assessments were carried out, and microbiological samples were collected, using concentrated oral rinse samples at 3 time points: baseline, 3 months, and 6 months. Results: The prevalence of oral yeast was significantly reduced in the test group at 6 months (P <.05), but no significant difference was observed over time. A significant reduction was observed in the prevalence of Staphylococcus aureus (P <.01) and aerobic and facultative gram-negative bacilli over time (P <.05), but there were no significant differences noted between groups at 6 months. Candida albicans and Klebsiella pneumoniae were the prominent pathogens determined throughout the trial. Kluyvera strains have also been isolated from this cohort. Conclusion: Oral hygiene intervention using a powered tooth brush and 1% chlorhexidine oral gel was effective in reducing the prevalence of oral opportunistic pathogens. 2017 Elsevier Inc.